Analysis of the Trends in Temperature and Rainfall in Thika River Basin in Kenya - Macharia, Michael Maina; Raude, James Messo (International Journal of Climate Research, 2017)
The Thika River catchment is of great importance to Kenya and holds Ndakaini Dam where about 84% of Nairobi’s water supply comes from serving a population of over 3 million residents, whose contribution to Kenya’s Gross Product is 60%. The evidenced climate variability and trends for Thika catchment were assessed for significance using the Man Kendall’s trend test and discussed based on future climate variability scenarios. The results showed that the catchment has become relatively warmer over the past four decades. The annual precipitation and means of daily mean temperatures over the past 30 years has increased by about 7.8 mm (although not statistically significant), and 2.14°C respectively.